Estimation of the mixed system reliability function using the Pareto and Rayleigh distributions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research dealt with the study and analysis of mixed working systems by employingsimulation experiments in Estimation the reliability function of the mixed system by usingsample sizes and values of different hypothetical parameters on the assumption that the life timeof the compounds are distributed Pareto distribution and Rayleigh distribution. The comparisoncriterion was adopted on the statistical scale (average of integral error squares) in order todetermine the priority of each method through the results that were reached